2018
DOI: 10.1155/2018/6364821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Redox Disturbances on Intestinal Contractile Reactivity in Rats Fed with a Hypercaloric Diet

Abstract: Few studies have associated the effects of changes in caloric intake and redox disturbances in the gastrointestinal tract. Therefore, the present study aimed at evaluating the hypercaloric diet consumption influence on the contractile reactivity of intestinal smooth muscle, morphology, and oxidative stress of rat ileum. Wistar rats were randomly divided into groups that received a standard diet and fed with a hypercaloric diet for 8 weeks. Animals were euthanized, and the ileum was isolated to isotonic contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…It has recently been shown that food supplementation with S. platensis promotes beneficial effects on the NO signaling pathway in the aorta of healthy rats [ 8 ], reduces oxidative stress and body adiposity in obese rats ileo [ 40 ], and prevents damage caused by a hypercaloric diet in erectile function [ 41 , 42 ], highlighting the promising role of seaweed in the prevention of various organic and metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that food supplementation with S. platensis promotes beneficial effects on the NO signaling pathway in the aorta of healthy rats [ 8 ], reduces oxidative stress and body adiposity in obese rats ileo [ 40 ], and prevents damage caused by a hypercaloric diet in erectile function [ 41 , 42 ], highlighting the promising role of seaweed in the prevention of various organic and metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, supplementation with S. platensis completely prevented the decrease in both the potency and the relaxing effectiveness of the electromechanical component, bringing them back to what was observed in the control group, confirmed by the overlapping curves. Likewise, the hypercaloric diet reduced the contractile effectiveness of KCl, proving that it reduces the contractions caused by electromechanical coupling [ 33 ]. In contrast, Ferreira [ 27 ] did not observe any difference between animals fed a standard diet supplemented with S. platensis in relation to the obese group, and it is not possible to observe a reversal of such effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Souza et al [33] found that Wistar rats fed for 8 weeks on a hypercaloric diet showed reduced intestinal contractile efficacy compared to KCl and CCh. Thus, once the onset of obesity was confirmed and a reduction in ileal contractile reactivity was verified, the hypothesis was raised that 9 Oxidative Medicine and Cellular Longevity the consumption of the hypercaloric diet could decrease the contractile response to CCh by negatively modulating the muscarinic receptors present in the intestinal smooth muscle and that by its antioxidant role, supplementation could prevent this modulation by possibly acting on calcium influx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations